2020
DOI: 10.1002/ijgo.13186
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women’s knowledge and practice of preventive measures against COVID‐19 in a low‐resource African setting

Abstract: the virus that causes it has spread to over 110 countries, including Nigeria. 1-3 Although the impact of COVID-19 on pregnant women is not yet clear, there are concerns over its potential effect on maternal and perinatal outcomes due to unique immunological suppression during pregnancy. 4,5 The World Health Organization (WHO) has recommended a series of preventive measures to halt the spread of the disease and its associated mortality. 3 In Nigeria, these preventive measures have been adopted, along with medi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
45
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 4 publications
10
45
6
2
Order By: Relevance
“…The level of knowledge of pregnant women who had more children was signi cantly higher, and although nonsigni cant, their risk perception was lower and their preventive behavior was better. Contrary to our study, in the study of Nwafor et al, pregnant African women who had given birth ve or more times had lower levels of awareness about preventive measures related to COVID-19 [24]. The greater awareness of pregnant women with a previous history of in uenza in the present study can be related to the increased sensitivity of this group of women to the risk of contracting viral diseases during pregnancy and its complications.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The level of knowledge of pregnant women who had more children was signi cantly higher, and although nonsigni cant, their risk perception was lower and their preventive behavior was better. Contrary to our study, in the study of Nwafor et al, pregnant African women who had given birth ve or more times had lower levels of awareness about preventive measures related to COVID-19 [24]. The greater awareness of pregnant women with a previous history of in uenza in the present study can be related to the increased sensitivity of this group of women to the risk of contracting viral diseases during pregnancy and its complications.…”
Section: Discussioncontrasting
confidence: 99%
“…According to our study, women with a university education were signi cantly more aware of the disease than women with less education. In the recent study of Nwafor et al, one of the factors associated with inadequate knowledge of preventive measures regarding COVID-19 was no formal education [24]. The level of knowledge of pregnant women who had more children was signi cantly higher, and although nonsigni cant, their risk perception was lower and their preventive behavior was better.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It seems that the awareness of pregnant women, both through the mass media and by health care providers, has increased significantly. In a study by Nwafor et al, 60.9% of pregnant women had sufficient knowledge of preventive measures against COVID-19 [24]. Yassa et al, in their study on pregnant women near childbirth, found that pregnant women have a positive attitude toward quarantine.…”
Section: Discussionmentioning
confidence: 97%
“…Protective measures were adopted by most pregnant women in China [12], whereas practice of preventive measures was poor among pregnant women in Nigeria [13]. Population's mental health and behavior are both important in preventing infectious diseases [14]. Psychological distress of pregnant women can also affect their own health and the physiological, cognitive, and psychological development of their offspring [15].…”
Section: Introductionmentioning
confidence: 99%